Efeitos de sentido de figuras de linguagem no gênero anúncio publicitário: uma abordagem dialógica - Nunes, Darcijane dos Santos (2014)
This research will show what are the sense effects produced by figures of speech in advertisement gender. Considering that, the figures of speech are more studied in literature and there are not many works about this theme found in discursive field, we try to develop a research that allow to see the importance of the figures of speech to the sense production of the discourse, especially, in advertisement gender. We used as theoretical reference, the works developed by researchers of the discursive area based on Bakhtin, like Beth Brait (2006), CristovãoTezza (2001), Augusto Ponzio (2009) and others researchers that agree with Bakhtin’s idea. As theoretical category we will use the notion of enunciate, discursive gender, stile and polyphony proposed by Bakhtin (2010), as well as the conception of the ideological sign proposed by Voloshinov (1997). For that, we try to show the discursive character of the phenomenon above mentioned, for that, we did a theoretical journey in Bakhtin’s study about the conception of language, dialogic, enunciate, ideological sign, polyphony, discursive gender and stile. This is a bibliographic, explanatory and documental research, and is about the analysis of the sense produced by the figures of speech in advertisement gender, this theme also embrace the analysis of linguistic phenomenon and no linguistic, like, metaphors, metonymy, personification, images, colors and extra verbal elements, like, the position of readers/ consumer and producer/author in relation of the announced advertisement and the situational context. We tried to show, with this research, that the meaning are built in a social and historical way, and when we analyzed them through the enunciatively-discursive prism, we can see multiple meanings that are only possible to be revealing when we consider the extraverbal elements ( Visual elements, social and historical context and the subjects that are involved in the discourse), because the word, does not bring itself the expressive cargo and, when people doing a structural analysis, they do not consider the most important part of the enunciate that promotes the sense effects.